Peran Guru dalam Kebijakan Kurikulum Merdeka di Sekolah - Vivi Sumanti; Firman Firman; Riska Ahmad (Keguruan, 2022)
Education always keeps up with the times and the curriculum always changes according to the needs of the times. The purpose of this study is to analyze the state of education through curriculum policy changes to improve the quality of education in Indonesia. This study uses qualitative research methods and a type of literature review. The author uses data collection techniques by collecting and analyzing information from sources that are relevant to the discussion. Once collected, the data were analyzed using descriptive methods. Based on the sources examined, the facts of the events written in the statement were revealed. The findings of this study are changes due to new curriculum policies that affect the teacher's role, as well as pedagogic challenges that require teachers to be rooted in their own expertise to develop learning with this new curriculum